PEMBELAJARAN BERBASIS REACT UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS X PADA MATERI FUNGSI EKSPONENSIAL DI SMAN 2 BATU - Wiwik Sugiarti; Marhan Taufik; Alfiani Athma Putri Rosyadi; Arif Hidayatul Khusna; Rizal Dian Azmi (INSPIRAMATIKA, 2018)
Mathematics learning is a subject that prioritizes strong conceptual understanding. This makes the teachers have to use the right model and strategy in conveying to the students that understanding the concept can be optimal. So that the learning in this study uses the REACT strategy. This strategy links teaching material with circumstances around. By using this REACT strategy in learning there is an increase in students' understanding of exponential function material with the REACT approach. This is indicated by the change in test score I, which is 62 to 82 in the second test. In addition, it can also be seen from the results of a questionnaire that shows an increase in student understanding.